HUBUNGAN PENGETAHUAN DAN SIKAP IBU NIFAS TENTANG PERAWATAN LUKA PERINEUM DENGAN PENYEMBUHAN LUKA PERINEUM DI WILAYAH KERJA UPT. PUSKESMAS GAJAH MADA DAN WILAYAH KERJA UPT. PUSKESMAS TEMBILAHAN HULU - Nurul Indah Sari , Lisa (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Perineum wound is the area which is diffcult to maintain to keep it dry and clean. Special observation and treatment is needed to ensure the area can heal by doing proper perineum care and it will cause infections complications due to errors in perineum wound care. From initial survey that was done by doing interview method in Public Healt Center of Gajah Mada and Tembilahan Hulu with 6 patients (100%) only knew how to treat perineum wound by changing sanitary pads at least twice a day whitout washing hands before and after doing treatment perineum wound. This research design is anlytic observational by using cross sectional approach. The popolation in this research is puerperium mother is 2019 in UPT of public Healt Center Gajah Mada and Tembilahan Hulu with total per month is 134 persons. Taking sampel by using accidental sampling by the amount 32 persons. Data collecting tool is using cheklist sheet of observation sheet. The test result chi square in knowledge and attiude of perineum mother toward perineum wound treatment and perineum wound healing was obtain 0,000 it means there is relationship between knowledge and attiude of perineum mother toward perineum wound treatmen and perineum wound healing. It is expected to increase perineum mother’s knowladge by doing promotive effort like counseling at first visiting on puerperium period by using media that can be brought to go home by patients like brochurenor leaflet so that patiens can read again after they are at home.